How @catchmeupid Utilizes Code-mixing in Its News Headlines and Headings: Types, Motives, and Identities - Muflihatunnisa; Agung Nugroho, Suray (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This descriptive qualitative research discusses the relationship between code-mixing written in the selected news headlines and headings; and the identities of the reporter at the Twitter account @catchmeupid. This paper attempts to examine 1) the types and motives of the @catchmeupid reporter in implementing code-mixing and 2) what kinds of identities he wants to portray. The code-mixing is collected with the documentation technique from news about a murder case committed by Ferdy Sambo. The research found 46 instances of 38 headings and 8 headlines from the news. The data were in the form of words, phrases, and sentences. The code-mixing is analyzed by the framework of Muysken for the types, Ritchie and Bhatia’s for the motives, and Fairclough’s text analysis for the identities. The results revealed that the salient processes of code-mixing types are insertion (29 instances) and alternation (17 instances), with no data for congruent lexicalization. The motives for code-mixing are the reporter’s awareness of their target audience, the willingness of the reporter to set an informal interaction with the target audience, the reporter’s emphasis on message-intrinsic considerations by using reiterations, interjections, and an idiom; and the reporter’s positive attitude in using the combination of Indonesian and English language. As for the identities, there are two identities demonstrated by @catchmeupid. Firstly, it is an identity as a news reader. @catchmeupid wants to be identified as the millennial/Z Generation who is familiar with English and as an ordinary citizen who is critical and interested in the settlement of the Ferdy Sambo case. Secondly, the identity as a news reporter who was knowledgeable and persuasive; and had an equal position to the other parties referred to in the news texts. Overall results indicated that the use of code-mixing by @catchmeupid’s reporter was related to the identities they wanted to portray.